Food as Destination: Cultural Delicacies as Motivating Factor for Tourists to Travel - Roseanne A Valino; Precil Nicole G Canoy; Marinel Pearl A Lopez; Samantha Mae C Sumang; Kenneth M Agao; Rovena I Dellova (Humanities, Society, and Community, 2025)
What makes a destination iconic has something to do with the unique experience of the tourist, whether seeking novelty or popularity in new places. This study aimed to gain a thorough understanding of tourists’ motivating factors in choosing cultural delicacies as the basis of their travel destination. This utilized a quantitative research design using a descriptive approach. Data were gathered from 376 res9pondents using snowball sampling, and the results were analyzed using frequency distribution, weighted mean, and analysis of variance (ANOVA). The majority of the respondents are female (62%), aged 30 years and below (79.8%), and from Manila (25.5%). The findings revealed that tourists are concerned about cultural delicacies’ characteristics in taste, freshness of ingredients, and visual appearance, all labeled as "very important." In terms of the importance of cultural delicacies, the respondents perceived them as "very important", while in terms of the factors affecting the tourists’ motivation, the three primary influencing factors are price, health concerns, and religion. All respondents, despite their gender, age, and location, have a similar assessment of these characteristics as motivating factors for them to travel. Price is an important consideration when choosing delicacies, followed by health and religion. The respondents have similar assessments of the significant difference between the importance of cultural delicacies and their profile. However, age differences are significant. The study shows that acknowledging budget-friendly, healthy, and religious dietary choices in a delicacy is an important consideration for tourists when they travel. They are increasingly exposed to motivators, leading to satisfaction and loyalty. The study has limitations, generalizing the food characteristics and identifying pull factors for tourists to travel. Hence, future studies are recommended to specify a particular delicacy associated with the identified destination and to explore the impact of cultural delicacies to attract tourists that are sustainable, thereby promoting the destination brand in the Philippines.